2008
DOI: 10.17796/jcpd.33.2.d0kwj02t525t8177
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Bone Density in Adolescents and Young Women with Anorexia Nervosa

Abstract: Purpose-To evaluate the dental and periodontal health of adolescents and young women with restrictive anorexia nervosa (AN), and relationship between bone mineral density (BMD) assessed by dual energy X-ray absorptiometry (DXA) and dental radiographs.Study Design-Twenty-three young women, median age 17.6 years (range 14.4-27.2), were studied within three months of entering a clinical trial. DXA BMD measurements were obtained and subjects underwent a comprehensive dental examination, including panoramic and bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…Twenty papers were published in English [4][6], [9], [18]–[26], [28], [30]–[32], [34][36], and there were also publications in Portuguese [29], Spanish [27] and Italian [33]. The search presented papers published from 1977 [25], [26] to 2013 [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty papers were published in English [4][6], [9], [18]–[26], [28], [30]–[32], [34][36], and there were also publications in Portuguese [29], Spanish [27] and Italian [33]. The search presented papers published from 1977 [25], [26] to 2013 [6].…”
Section: Discussionmentioning
confidence: 99%
“…It also did not mention if the patients were referred from hospitals [25]. Only a few studies reported the criteria used to identify TE or if the examiners had been trained and calibrated [6], [9], [25], [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be pointed out that in this study, 26 % of the participants had history of binge eating/vomiting activity [ 45 ]. A recent systematic review showed that patients with eating disorders who have a self-induced vomiting habit showed 19.6 times more risk for erosion than patients without vomiting habits [ 28 ].…”
Section: Eating Disordersmentioning
confidence: 57%
“…The malnutrition and related medical complications resulting from ED such as AN, BN, and eating disorder not otherwise specified may have more severe and potentially more protracted consequences during youth than during other age periods. The Workgroup for Classification of Eating Disorders in Children and Adolescents (2010) and The Society for Adolescent Medicine recommend that the diagnoses and treatment thresholds for pediatric ED should be lower than for adults due to the potentially irreversible effects of ED including pubertal delay, growth retardation, short stature, structural brain changes, low bone mineral density (6,7). In addition, it has been reported that in young women suffering from BN, unstimulated saliva flow rate was decreased, with frequent complaints of dry mouth (8).…”
mentioning
confidence: 99%